The fiscal implications of public service productivity - Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
The challenging fiscal situation facing the next government means that both Labour and the Conservatives are looking for ways to improve public services without large increases in spending. Improving the productivity of public services is often proposed as a way to achieve this. This follows the big fall in measured productivity of government services - particularly in the NHS (Warner and Zaranko, 2023) - since the start of the pandemic. In the March 2024 Budget, the Chancellor, Jeremy Hunt, launched a new 'Public Sector Productivity Plan' and argued that 'the way to improve public services is not always more money or more people - we also need to run them more efficiently' (HM Treasury, 2024). Mr Hunt set out 4.2 billion of funding to improve the productivity of public services, including 3.4 billion for the NHS. In this report, we consider the current state of public service productivity and make two arguments about the potential fiscal implications of any future improvements.
Keywords: 330; Government finances and spending; Government spending; Productivity; Public finance; Public sector